Herding behavior and market bubbles : A behavioral finance perspective - Pitkäkoski, Iris (My University, 2025)
This thesis examines the relationship between herding behavior and market bubbles from a behavioral finance perspective. The paper discusses how different biases, social influence, and informational cascades affect investor decision-making, often leading them to mimic others rather than relying on their private information. This study aims to examine the situations where herding is the most common, such as periods of high uncertainty and volatility in the financial markets. At the core of the paper is the model of Cross-Sectional Absolute Deviation (CSAD), which is used to detect the presence of herding behavior in financial markets. The goal is to understand how herding is currently empirically tested and explore if patterns of herding could be an early warning or indicator of specific circumstances that contribute to speculative market bubbles. The findings of this thesis suggest that herding has a significant role in increasing asset mispricing and market volatility. Therefore, it could contribute to the formation of financial instability, such as speculative market bubbles. This makes it important for investors and regulators to be aware of these risks, since there is a need for improved market transparency and investor education to reduce the likelihood of future bubbles forming.

Tässä tutkielmassa tarkastellaan sijoittajien laumakäyttäytymisen ja markkinakuplien välistä yhteyttä käyttäytymistaloustieteen ja rahoitusteorioiden näkökulmasta. Tutkielma keskittyy siihen, kuinka sosiaalinen vaikutus ja informaatioketjut voivat johtaa sijoittajia jäljittelemään toistensa käyttäytymistä, joka usein poikkeaa heidän omasta perustuvanlaatuisesta tiedostansa. Tavoitteena on analysoida tilanteita, joissa laumakäyttäytyminen on erityisen voimakasta rahoitusmarkkinoilla, kuten epävarmuuden ja suuren volatiliteetin aikana. Tutkielman keskiössä on Cross-Sectional Absolute Deviation (CSAD) -malli, jota käytetään laumakäyttäytymisen havaitsemiseen rahoitusmarkkinoilla. Tutkimuksen tavoitteena on ymmärtää, miten laumakäyttäytymistä tällä hetkellä empiirisesti mitataan sekä tarkastella, voiko mallin avulla havaita varhaisessa vaiheessa olosuhteita, jotka edistävät spekulatiivisien markkinakuplien muodostumista. Tutkielman tulokset osoittavat, että laumakäyttäytymisellä on merkittävä vaikutus hinnoitteluvirheiden ja volatiliteetin voimakkuuteen, mikä voi kasvattaa epävakautta rahoitusmarkkinoilla. On tärkeää, että sijoittajat ja viranomaiset ovat tietoisia mahdollisista riskeistä, jotta markkinoiden avoimuutta ja sijoittajien koulutusta voidaan parantaa ja täten tulevien markkinakuplien muodostumisen todennäköisyyttä voidaan vähentää.
Keywords: extrapolation; decision making; herding; investor communication; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|